Effectiveness of Early Childhood Online Learning - Warni Holiza; Rakimahwati (Bisma The Journal of Counseling, 2022)
This research was conducted to examine the effectiveness of the implementation of learning in early childhood networks at Umbuik Nagari Kindergarten. The purpose of this research is to effectively implement learning in early childhood networks at Umbuik Nagari Kindergarten. This study uses a qualitative research design with interview techniques to obtain an overview of the learning system at Umbuik Nagari Kindergarten. In this study, the data collection techniques required used the interview, documentation, and observation methods. Then the data were analyzed descriptively. From the research findings that there is no online learning curriculum, limited supporting infrastructure, the ability of educators who are technologically stuttering, lack of communication between educators and parents, lack of support from parents to carry out the online learning process, many parents who do not have outdated communication tools. information, children's interest in learning decreases.